2009
DOI: 10.1002/cmdc.200900045
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Disease Modifiers—PKC Activation and HDAC Inhibition—A Dual Drug Approach to Alzheimer's Disease that Decreases Aβ Production while Blocking Oxidative Stress

Abstract: Alzheimer's disease (AD) is a well-studied process characterized by the presence of amyloid plaques and neurofibrillary tangles. In this study, a series of protein kinase C (PKC) activators were investigated, some of which also exhibit histone deacetylases (HDACs) inhibitory activity, under the hypothesis that such compounds might provide a new path forward in the discovery of drugs for the treatment of AD. The PKC activating properties of these drugs were expected to enhance the α-secretase pathway in the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…In this regard, the antiinflammatory properties of HDACi's appear to be neuroprotective. In animal models of Alzheimer disease, the most studied neurodegenerative disease, HDAC inhibition decreased β-amyloid production and effective neuroprotection was associated with increased acetylation of histone 4 (94). In a model of closed head trauma, the antiinflammatory properties of HDACi's prevented the deterioration of neurological impairment, even when administered 24 hours after the injury (93).…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…In this regard, the antiinflammatory properties of HDACi's appear to be neuroprotective. In animal models of Alzheimer disease, the most studied neurodegenerative disease, HDAC inhibition decreased β-amyloid production and effective neuroprotection was associated with increased acetylation of histone 4 (94). In a model of closed head trauma, the antiinflammatory properties of HDACi's prevented the deterioration of neurological impairment, even when administered 24 hours after the injury (93).…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…The structurally simplest member of the family is (-)-indolactam V (ILV, 34), which can be produced in large quantities in Actinomycetes and has therefore been used as a starting point for the synthesis of new derivatives [58]. Several groups -the Irie, the Kozikowski, and the Endo groups -have carried out research into these compounds, revealed important structure-activity relationships and developed novel indolactam and benzolactam derivatives with improved selectivity profiles (see, for example, [133][134][135]). …”
Section: Indo-and Benzolactamsmentioning
confidence: 99%
“…61,62 We thus explored whether bizine might confer neuroprotection against HCA-induced oxidative stress. Indeed, 0.5 µM bizine led to significantly enhanced survival of neurons after HCA treatment in a dose-dependent fashion (Figure 7A,B).…”
Section: Resultsmentioning
confidence: 99%